A Purification Process of Wosting Oil Using CaO Adsorbent Based on Blood Shell Shells (Anadara granosa) - Nafsiatil Afro', Maulina; Rahayu, Susi; Ardianto, Teguh; Wijaya Kurniawidi, Dian (Jurnal Biologi Tropis, 2025)
Blood clam shells are inorganic materials rich in  content obtained from heating  at high temperatures, so they can be used as adsorbent. The purpose of this study is to determine the effect of calcination temperature of blood clam shell adsorbents, used to test the quality of used cooking oil (wosting oil). In this study, three calcination temperature variations were used, namely 800 ℃, 900 ℃ and 1000 ℃ for 2 hours each. Then the quality of adsorbent was tested by knowing oxide element with SEM. The adsorption process was carried out using the contact method by immersing the adsorbent in wosting oil for one hour. Wosting oil that has been adsorbed is then tested for quality, namely: free fatty acid content, peroxide number, water content, viscosity, density, physical properties (odor and color). The results obtained are: The best quality of  adsorbent was obtained at a calcination temperature of 1000 ℃ which was analyzed through three parameters namely,  content, density value and surface area. The best quality of wosting oil is obtained in used cooking oil with 3 times heating with calcined adsorbent at 1000 ℃ which is analyzed based on several parameters as previously explained.